(untitled) (Світ фінансів, 2017)
Горин В. П. Концептуальні засади фінансового забезпечення соціальних гарантій. Узагальнено існуючі концептуальні підходи до визначення поняття “фінансове забезпечення соціальних гарантій”. Розглянуто форми фінансового забезпечення, на основі запропонованої класифікації соціальних гарантій виокремлено відповідні напрями їх фінансування. Horyn V. Conceptual principles of social guarantees financial providing. The existent conceptual approaches to the interpretation of financial providing of social guarantees. The forms of the financial providing are considered and on the basis of the offered classification of social guarantees the proper directions of their financing are selected.